"Deaths in Prison Custody" Capstone Course: Engaging Final-Year Law Students In Service Learning and Public Value. Issue 3 (2nd July 2016) - Kilcommins, Shane; Spain, Eimear
Abstract : Capstone service learning courses are designed to overcome the negative effects of fractioned knowledge by enabling students to consolidate and apply what they have learned over a program of study. They also promote a scholarship of engagement. This article documents the learning experiences of students on a Deaths in Prison Custody capstone service learning course. Though such a criminal justice course requires significant staff input and involves some loss of educational control, it has many benefits including enhanced learning, meaningful service, public value, and civic engagement. The focus on this article is on student learning experiences. It outlines how the pragmatic focus of such a course made knowledge and student learning relevant and actionable. It also describes how the deliberately unstructured design of the course, together with its emphasis on pubic value, encouraged autonomous and self-directed learning, prompting the students to take greater ownership of their learning.